Answer:
5x + y = -48
Step-by-step explanation:
(y + 3)/(x + 9) =m
=> y + 3 = -5x -45
=> 5x + y + 48 = 0
Answer:
the motion of the object will stay the same
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
Because 15-4=11
and both angles are equal
Answer:
<h2>x = -1</h2>
Step-by-step explanation:
![x^2+5x+4=0\\\\x^2+x+4x+4=0\\\\x(x+1)+4(x+1)=0\\\\(x+1)(x+4)=0\iff x+1=0\ \vee\ x+4=0\\\\x=-1\ \vee\ x=-4](https://tex.z-dn.net/?f=x%5E2%2B5x%2B4%3D0%5C%5C%5C%5Cx%5E2%2Bx%2B4x%2B4%3D0%5C%5C%5C%5Cx%28x%2B1%29%2B4%28x%2B1%29%3D0%5C%5C%5C%5C%28x%2B1%29%28x%2B4%29%3D0%5Ciff%20x%2B1%3D0%5C%20%5Cvee%5C%20x%2B4%3D0%5C%5C%5C%5Cx%3D-1%5C%20%5Cvee%5C%20x%3D-4)
Answer:
(A:) I created a scatter plot similar to the one i used for mine, this is for the first part of your question
(B:) Positive Association
Step-by-step explanation:
(B:) Why? Because as your x value increases so does your y and it shows this with the data as well.
I had a tough time with this until i actually read through what it was really asking so i hope this helps you